Transforming justice responses to non-recent institutional abuses - McAlinden, Anne-Marie (Clarendon studies in criminology, 2025)
Over the last few decades, the issue of historical/ non-recent institutional abuses has resonated in a range of Western states and churches. Despite the recent proliferation of 'justice' responses to such abuses including prosecutions and civil litigation, inquiries, redress and apologies, it is a subject which is insufficiently understood in the literature. Set against the complexities of the legal, historical, cultural, and political realities of addressing non-recent institutional abuses, 'Transforming Justice Responses to Non-Recent Institutional Abuses' critically examines these justice responses across Northern Ireland and the Republic of Ireland.